Using Heuristic Evaluation to Enhance the Visual Display of a Provider Dashboard for Patient-Reported Outcomes. Issue 2 (20th April 2017) - LeRouge, Cynthia; Hasselquist, Mary Beth; Kellogg, Liz; Austin, Elizabeth; Fey, Brett; Hartzler, Andrea; Flum, David R; Lavallee, Danielle C.
Introduction: With the rising use of patient-reported outcomes (PRO) in clinical practice, there is an increasing need to understand the data visualization needs of clinical teams to support their effective use of PRO data for both individual patient decision making and broader population health applications. A human-centered design (HCD) approach can optimize the visual design of an interactive PRO system. Including Heuristic Evaluation in the HCD Toolbox: Recent literature regarding the use of HCD to design and develop PRO visualizations demonstrates the benefits of iterative methods that engage representative users who are likely to use the system in the future. However, the literature has not explored the additive value of other HCD methods such as heuristic evaluation, which involves expert examination of the interface with respect to recognized usability principles, the heuristics. Insights from Using Heuristic Evaluation: Our experience in using heuristic evaluation to enhance the design of a PRO dashboard led to several recommendations to improve the display, accessibility, and interpretability of the dashboard's data. Heuristic evaluation can serve as a complement to HCD methods that directly engage users and thereby enhance usability.